2020
DOI: 10.1002/jor.24716
|View full text |Cite
|
Sign up to set email alerts
|

Lower functioning patients demonstrate atypical hip joint loading before and following total hip arthroplasty for osteoarthritis

Abstract: Previous studies have established that up to 1 year post total hip arthroplasty (THA), patients do not recover normal function and the magnitude of hip joint loading remains reduced compared to healthy individuals. However, the temporal nature of the loading profile has not been considered to identify individuals who are at a greater risk of poor functional outcomes following THA. This study aimed to determine changes to the profile and magnitude of the resultant hip joint reaction force before and up to 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…This was combined with knowledge of the varied individual joint contact forces from gait examinations to inform tailored musculoskeletal modeling. The predicted forces were representative of a larger patient cohort 23 and are comparable to the joint contact forces reported in the literature. 40,41 While it is reasonable to speculate that improved representation of bone quality and loading conditions should improve FE estimates of bone stress and strain, further corroboration with in vivo or ex vivo experimental work will allow for further improvements in modeling.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This was combined with knowledge of the varied individual joint contact forces from gait examinations to inform tailored musculoskeletal modeling. The predicted forces were representative of a larger patient cohort 23 and are comparable to the joint contact forces reported in the literature. 40,41 While it is reasonable to speculate that improved representation of bone quality and loading conditions should improve FE estimates of bone stress and strain, further corroboration with in vivo or ex vivo experimental work will allow for further improvements in modeling.…”
Section: Discussionsupporting
confidence: 77%
“…22 Ideally, individual subject forces should be predicted using tailored musculoskeletal models. 23 Hence, the aims of our study were to: (1) develop coupled musculoskeletal-FE models for individuals who had received an uncemented acetabular component; and (2) validate the predictions of patient-specific FE models against RSA measured in vivo cup migration.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the reduction in the hip adduction moment was compensated with increased power generation in the ankle joint. However, the patients in the study of Kubota et al ( Kubota et al, 2007 ) had a very low walking speed (∼0.65 ms −1 ) so that the characteristic double peak was not visible in the hip adduction moment, which might indicate that patients with low functional status were studied ( Bahl et al, 2020 ). The patients in the present study walked at a speed similar to unilateral hip OA patients reported in various studies ( Foucher, 2017 ; Schmidt et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ground reaction force cannot be used as a surrogate for internal hip joint loading. However, reduced gait velocity and reduced hip flexion and extension range were significantly correlated with the prevalence of a single-peak profile [ 49 ]. After THA, passive ROM in the affected hip joint showed clear improvement.…”
Section: Discussionmentioning
confidence: 99%